A new species group of the genus Epicauta Dejean of Southern South America, the bella group (Coleoptera: Meloidae) - Campos Soldini, Maria Paula (2011)
Epicauta (Coleoptera: Meloideae) includes two subgenera, and within the nominotypical subgenus several species groups. Analyzing species of southern South America, a set of species of Epicauta has the particularity to present two distinctive characters which separates this group from the other species groups of American Epicauta: color pattern of pubescence in elytra is not coincident with color pattern of tegument and endophalic hook robust. Based on these characters I propose a new group of species herein named bella group. This group includes the Neotropical species Epicauta bella Mäklin, E. brunneipennis (Haag-Rutemberg), E. diagramma (Burmeister), E. griseonigra (Fairmaire), E. luctifera (Fairmaire), E. riojana (Fairmaire) (New status), and E. zebra (Dohrn). This group is endemic of southern South America, inhabiting the Chaco biogeographical subregion, mainly in the arid northern areas of Argentina. Here we redefine the species of the bella group, consider new characters, illustrate the species in the group, provide maps of their distribution, and a key to identify them.